Uses and desuses of the urban park on a metropolitan scale: A study of the users profile of tejo park in Lisbon (Portugal) - Gomes, Marcos Antônio Silvestre; De Oliveira, Jonatan Alexandre [UNESP] (Universidad Nacional de Colombia, 2020)
The parks compose urban agendas as spaces that legitimize environmental and social commitment. However, it is common to design these spaces in areas of great real state interest, as was the case with Tejo Park in the city of Lisbon. This work analyzes its implementation, between 1995 and 1999, as part of a broader urban project, called Park of the Nations, to host the 1998 World Exhibition of Lisbon. Tejo Park occupied an area with a high level of environmental degradation, contributing to the projection of a modern Lisbon, competitive in the global market of cities. The analysis deepens the debate of the proposal of a metropolitan scale park, whose uses would serve a diverse audience socially and spatially. The article highlights aspects of its infrastructures and the profile of its users, helping to a reading of the uses and appropriations and as a methodological path for studies of different realities. Thus, the results point to adornment characteristics to the Park of the Nations, contemplative leisure, without diversity of equipment, which has limited its uses and functions.
Usos y desusos del parque urbano en escala metropolitana: Un estudio del perfil de los usuarios del parque tejo en Lisboa (Portugal)
Usos e desusos do parque urbano em escala metropolitana: Um estudo do perfil dos usuários do parque tejo em Lisboa (Portugal)
Keywords: Infrastructures; Lisbon; Tejo park; Urban parks; Users